Triple bottom line, sustainability and economic development: Theoretical insights and the research agenda - Lopes, João M. (2022)
An analysis of the relationship between Triple Bottom Line (TBL), economic development (ED) and sustainability was undertaken to strengthen the extension of TBL’s dominant rhet- oric to sustainability- aligned ED and pave the way for new lines of research. We used the Web of Science database and gathered for analysis 37 publications, which simultaneously respected the keysearchterms:TripleBottomLine,EconomicDevelopment and Sustainability, to carry out a bibliometric analysis of the literature. Four clusters were identified and designated as: social development, social entrepreneurship, economic development and sustainability. This study includes an analysis of the evolu- tion of publications and citations, co-occurrence of keywords, identification of research lines and analysis of bibliographic coupling study. It also combats the scarcity of publications relating TBL, ED and sustainability. A table of research trends, a mapping of publications and the directions that should be followed by the academy are presented. The fact that the bibli- ometric literature review was based only on the Web of Science, the applied filtering process and the use of software may have omitted the literature. The need to expand TBL beyond the companies’ core business to more global concerns and a holistic study of TBL was identified.